The potential role of cyclosporine A in cancer treatment: a comprehensive literature review - Adnan Fojnica; Zehra Gromilic; Youssef Alaaeldin Ali Mohamed; Saghir Akhtar; Semir Vranic (Contemporary Oncology)
Cyclosporine A (CsA) is widely used as an immunosuppressant in organ transplantation to improve graft survival and prevent tissue rejection. The impact of CsA on cancer progression is highly complex, influenced by the intricate relationship between immunosuppression and malignancy. While individuals with compromised immune systems, notably organ transplant recipients, face an elevated risk of cancer invasion and progression due to immunosuppressive regimens, CsA’s role in either promoting or inhibiting cancer remains elusive. Divergent outcomes from in vitro and in vivo studies suggest suppression of cancer progression under CsA treatment and complicate the translation of findings to clinical scenarios. Despite promising in vitro and in vivo results, the clinical application of CsA in oncology necessitates careful consideration of its toxicity profile in in vivo models, starting at 50–200 mg/kg/d. The divergence between preclinical and clinical findings highlights the need for further research to elucidate the true nature of CsA’s impact on cancer, providing a foundation for more informed and targeted therapeutic approaches.